2008
DOI: 10.1177/0013916507311550
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Empirical Literature on the Relationships Between Indoor Environment and Stress in Health Care and Office Settings

Abstract: A conceptual framework linking indoor environment and stress is provided. The framework suggests that, in many cases, indoor environments may set forth a process leading to stress by affecting individual and/or workplace needs. The framework also suggests that because any direct causal relation between indoor environment and stress may be difficult to establish, researchers should focus more on the evidence that links indoor environment to individual and/or workplace needs. This review focuses primarily on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
167
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(180 citation statements)
references
References 158 publications
(174 reference statements)
5
167
0
8
Order By: Relevance
“…Rashid and Zimring [7], in their framework, suggested that indoor work environment may elicit stress "by the ways in which it affects individual and/or workplace needs.". For example, if an employee perceives that he/she need comfortable temperature to work, absence of such need would induce stress.…”
Section: Indoor Work Environment and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Rashid and Zimring [7], in their framework, suggested that indoor work environment may elicit stress "by the ways in which it affects individual and/or workplace needs.". For example, if an employee perceives that he/she need comfortable temperature to work, absence of such need would induce stress.…”
Section: Indoor Work Environment and Stressmentioning
confidence: 99%
“…Among predictors claimed to affect SBS and stress is the indoor work environment [7]. As most employees spend the majority of their time at the workplace, the indoor work environment might not only influences their physical wellbeing but also their psychological states.…”
Section: Introductionmentioning
confidence: 99%
“…Daylight is preferred by users because of its psychological and physiological effects. These effects are well documented, covering an area from improved health, well-being and productivity for the users, to significant building energy savings [1][2][3][4][5]. Lighting control systems can reduce energy use from electricity by 20% or even up to 60% in certain conditions [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The delivery of patient care in hospitals generates noise [1][2][3]. Emergency departments (EDs) are no exception and may even be particularly noisy due to the acute nature of patients' complaints, the typically high level of activity, and the considerable number of people simultaneously present.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency departments (EDs) are no exception and may even be particularly noisy due to the acute nature of patients' complaints, the typically high level of activity, and the considerable number of people simultaneously present. A noisy work environment makes it more difficult to communicate and perform cognitively complex tasks, and generally induces stress [3,4]. Thus, accurate knowledge of the noise level in EDs is important in order to assess this strain on the staff as well as the need for interventions to reduce it.…”
Section: Introductionmentioning
confidence: 99%